Aplikasi Analytic Network Process Pada Perancangan Sistem Pengukuran Kinerja dengan Menggunakan Metode Balanced Scorecard - S Sapto (Department Industrial Engineering, University of Muhammadiyah Malang, 2008)
Performance evaluation of company was very important to face competition with competitor and to be winner. So far, PT. Mitra Lestari Abadi conducted performance measurement at financial aspect and employee productivity, so that the company couldn’t identify factors caused reduce financial performance of company and performance of employee and also it didn’t know a part has to be repaired to increase performance on the next period. In solving the problem used Balanced Scorecard method as performance measurement system that translate vision and mission and strategy of company. From the result of performance measurement system design of PT. Mitra Lestari Abadi namely objective, key performance indicator and mapping strategy, it would be conducted heaviness with Analytic Network Process (ANP) method which considerate that there was relation each other among perspective and objective showed at map strategy. The result of performance measurement at PT. Mitra Lestari Abadi on a third of the year on 2007 with Higher is Better and Higher is Worse method and Traffic Light System was obtained all result KPI at PT Mitra Lestari Abadi with indicator green chromatic except to KPI amount of maintenance machine rotary, spindles, knife grinder and KPI amount of maintenance machine press dryer, composer, boiler with indicator yellow. Become management have to swiftly doing repair so that performance at next period progressively nicely.